2004
DOI: 10.3146/pnut.31.2.0008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cultivar and Plant Population on Spotted Wilt in Virginia Market-Type Peanut

Abstract: Field experiments were conducted in North Carolina during 2001 and 2002 to evaluate the impact of cultivar and plant population on the incidence of symptoms of tomato spotted wilt virus, which is transmitted primarily by tobacco thrips [Frankliniellafusca (Hinds) (Thysanoptera: Thripidae)]. Treatments included the virginia market-type cultivars Gregory, NC-V 11, and Perry seeded at in-row plant populations of 7, 13, and 17 plants/m. In these experiments, there was a consistent trend for increased foliar injur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
2
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
5
2
0
Order By: Relevance
“…When pooled over aldicarb treatments, VA 98R expressed greater damage from tobacco thrips feeding (1.9) compared with values of 0.8 to 0.9 for Gregory, Perry, and Phillips (data not shown). Differential response of peanut cultivars to damage from tobacco thrips has been reported previously (Hurt et al, 2004, 2005, 2006).…”
Section: Resultssupporting
confidence: 70%
“…When pooled over aldicarb treatments, VA 98R expressed greater damage from tobacco thrips feeding (1.9) compared with values of 0.8 to 0.9 for Gregory, Perry, and Phillips (data not shown). Differential response of peanut cultivars to damage from tobacco thrips has been reported previously (Hurt et al, 2004, 2005, 2006).…”
Section: Resultssupporting
confidence: 70%
“…While the main effect of plant stand was not significant for TSWV incidence (Table 4), there was a significant negative linear trend indicating that for every unit increase in plant stand, TSWV incidence decreased by 0.4 percentage points (Figure 2). This reduction in TSWV as plant stand increased is similar to findings in multiple other studies (Gorbet and Shokes, 1994;Wehtje et al, 1994;Culbreath et al, 1999;Hurt et al 2004).…”
Section: Resultssupporting
confidence: 90%
“…Chin Choy et al (1982) found no differences for TSMK values between seeding rates of 7, 15, and 22 viable seeds/m while Knauft et al (1981) showed a significant difference in grade in only one of six cultivars when varying plant population. Hurt et al (2004) reported mixed results with a 7 plants/m stand having a higher TSMK than a 17 plants/m stand in two of five experiments, the greater stand having a higher TSMK in two of five experiments, and no difference in TSMK in the fifth experiment.…”
mentioning
confidence: 94%
“…Similar trends have been reported for thrips injury with less injury observed as plant populations increased (Hurt et al, 2004(Hurt et al, , 2005(Hurt et al, , 2006. In these previous studies, all plantings received aldicarb or phorate in the seed furrow at planting; thus the effect of plant population was not considered independent of insecticide effects (Hurt et al, 2004(Hurt et al, , 2005(Hurt et al, , 2006. It has been hypothesized that increased peanut populations creates canopy closure earlier and does not allow thrips to locate the host plant as easily (Culbreath et al, 2003;Hurt et al, 2006).…”
supporting
confidence: 64%
“…Greater TSW incidence was noted when peanut was established at lower populations compared to higher populations (Black et al, 1994;Branch et al, 2003;Culbreath et al, 2013;Gorbet and Shokes, 1994;Lassiter et al, 2016;Tillman et al, 2006;Tubbs et al, 2011;Wehtje et al, 1994). Similar trends have been reported for thrips injury with less injury observed as plant populations increased (Hurt et al, 2004(Hurt et al, , 2005(Hurt et al, , 2006. In these previous studies, all plantings received aldicarb or phorate in the seed furrow at planting; thus the effect of plant population was not considered independent of insecticide effects (Hurt et al, 2004(Hurt et al, , 2005(Hurt et al, , 2006.…”
mentioning
confidence: 78%